Cyclopalitins A and B, nortriterpenoids from aerial parts of Cyclocarya paliurus. (June 2019) - Peng, Wenwen; Zhao, Simeng; Ji, Changjiu; Huo, Guanghua; Wan, Chunpeng; Li, Yuyan; Zhang, Yanling
Graphical abstract: Highlights: Two new triterpenes, cyclopalitins A and B (1 and2 ), were isolated from stems and leaves of Cyclocarya paliurus . Cyclopalitins A and B were two novel trinordammarane triterpenoids. Compounds1 and2 were tested for their cytotoxicity against B16F10. Abstract: Two novel nortriterpenoids, cyclopalitins A and B (1 and2 ), were isolated from aerial parts of Cyclocarya paliurus . Their structures were elucidated on the basis of extensive spectroscopic analyses including high-resolution electrospray ionization mass spectrometry (HR-ESI-MS), 1D NMR and 2D NMR. Compounds1 and2 were tested for their cytotoxicity towards B16F10. The results revealed that they didn't show cytotoxic activity against B16F10 with 10 ug/mL treatment for 48 h.